Melancholy and Crisis Worldview as the Situation of Man “In His Time” in the First Third of the XX Century - D. V. Andreenko (Дискурс, 2021)
Introduction. Shaping modernity in the first third of the twentieth century is tied to the private worldview of the person of this era in which the main metaphor of the individual perception of “their time” is melancholy. The crisis of this historical period forms the prism of melancholic worldview. The goal of this article is to substantiate the reasons for the perception of melancholy as a phenomenon caused in part by the problem of individual experience of time. The relationship between melancholy and modernity has already been noted in the literature, but this text raises a new question – what is the temporal nature of this mutual influence?Methodology and sources. A key role in the understanding of melancholy is played by the texts of authors of the early 20th century: Walter Benjamin, devoted to Charles Baudelaire and the work of Sigmund Freud “Mourning and Melancholy”. The issue of temporality in the work is interpreted through the reference to the phenomenological tradition, namely in reference to the modern phenomenological analysis of depressive disorder in the work of Domonkos Sik.Results and discussion. The author comes to the conclusion that the feeling of the interrelation of melancholy and the epoch is extremely specific for a person of the first third of the 20th century, evidence of which could be found in the philosophical and cultural reflection of this period. Crisis worldview is reflected in literature, painting, cinema, philosophy, social theory, etc. Thus, it is possible to represent melancholy as a phenomenon, partly caused by the problem of individual experience of time. Melancholy occurs when a crisis worldview is supplemented by an experience of circular temporality, the disappearance of the future, preoccupation with the past, passivity, or isolation.Conclusion. If these elements come together, a total worldview is formed in which real world events intensify melancholy. In this sense, phenomenologically speaking, melancholy is not so much a state as a dynamic process.